Exploring decision-making practices during coaching sessions in grassroots youth soccer: a mixed-methods study - Roca, A.; Pocock, C.; Ford, P. R. (Science and Medicine in Football, 2025)
Decision-making ability in players during match-play is mostly acquired through practice activities with the same underlying structure as competition. However, researchers have not fully investigated how coaches design practice sessions at the participation level of the sport (i.e. `grassroots`), or why they use a particular activity at a specific time point. This study explores the practice activities employed by youth soccer coaches at the participation level in England and aims to understand their underlying intentions. Twelve male coaches working with players aged 9-11 years across ten clubs in the London region participated. Thirty-five practice sessions were filmed and analysed to assess the proportion of time spent in activities involving `non-active decision-making` (e.g., technical practices, fitness training) versus `active decision-making` (e.g., small-sided and conditioned games, skills practice with realistic opposition). A brief on-field interview with the coaches about the session purpose took place immediately after each systematic observation. Coaches allocated similar amounts of time to activities with active (M = 41%) and non-active (M = 42%) decision making, with the remaining 17% being transitions. There was a common progression from non-active decision-making activities early in the session towards increased active decision-making later in the session. Interviews with coaches revealed a belief in the necessity of frequent non-active decision-making practices for technique development, despite potential disparities with improving match performance. Findings highlight a potential gap between scientific understanding and coaching practices for young soccer players at the participation level, suggesting implications for coach education programmes and the optimisation of player development strategies.